Results 1 to 4 of 4

Thread: Sum

  1. #1
    Newbie
    Joined
    Aug 2009
    Posts
    2

    Sum

    How to prove that $\displaystyle \sum_{m=0}^n\binom{2n}{2m}9^{n-m}=\frac12\big(4^{2n}+2^{2n}\big)$ ?
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor red_dog's Avatar
    Joined
    Jun 2007
    From
    Medgidia, Romania
    Posts
    1,252
    Thanks
    5
    Let $\displaystyle S_1=\sum_{m=0}^nC_{2n}^{2m}9^{n-m}=\sum_{m=0}^nC_{2n}^{2n}3^{2n-2m}$

    $\displaystyle S_2=\sum_{m=1}^nC_{2n}^{2m-1}3^{2n-2m+1}$

    Then

    $\displaystyle S_1+S_2=(3+1)^{2n}=4^{2n}$

    $\displaystyle S_1-S_2=(3-1)^{2n}=2^{2n}$

    Add the equalities:

    $\displaystyle 2S_1=4^{2n}+2^{2n}\Rightarrow S_1=\frac{1}{2}(4^{2n}+2^{2n}$
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Newbie
    Joined
    Aug 2009
    Posts
    2
    Thanks but, I don't see how did you get $\displaystyle S_1+S_2=(3+1)^{2n}$ ? I can't follow that equality, I was trying to figure out by myself but I couldn't.
    Follow Math Help Forum on Facebook and Google+

  4. #4
    MHF Contributor Amer's Avatar
    Joined
    May 2009
    From
    Jordan
    Posts
    1,093
    Quote Originally Posted by Soldado View Post
    Thanks but, I don't see how did you get $\displaystyle S_1+S_2=(3+1)^{2n}$ ? I can't follow that equality, I was trying to figure out by myself but I couldn't.
    $\displaystyle S_1+S_2 =\sum_{m=0}^{n} \left(\begin{array}{c}2n\\2m\end{array}\right) 3^{2n-2m} + \sum_{m=1}^n \left(\begin{array}{c}2n\\2m-1\end{array}\right) 3^{2n-2m+1} $


    lats expand S1

    $\displaystyle \sum_{m=0}^{n} \left(\begin{array}{c}2n\\2m\end{array}\right) 3^{2n-2m} = 3^{2n} + \left(\begin{array}{c}2n\\2\end{array}\right)3^{2n-2} + \left(\begin{array}{c}2n\\4\end{array}\right) 3^{2n-4} + ... +\left(\begin{array}{c}2n\\2n-2\end{array}\right)3^2 $

    S2 in the same way

    $\displaystyle \sum_{m=1}^n \left(\begin{array}{c}2n\\2m-1\end{array}\right) 3^{2n-2m+1} = \left(\begin{array}{c}2n\\1\end{array}\right)3^{2n-1} + \left(\begin{array}{c}2n\\3\end{array}\right)3^{2n-3} +... + \left(\begin{array}{c}2n\\2n-1\end{array}\right)3 $

    $\displaystyle S_1 + S_2 = 3^{2n} +\left(\begin{array}{c}2n\\1\end{array}\right)3^{2 n-1} + \left(\begin{array}{c}2n\\2\end{array}\right)3^{2n-2} +$$\displaystyle \left(\begin{array}{c}2n\\3\end{array}\right)3^{2n-3} +\left(\begin{array}{c}2n\\4\end{array}\right) 3^{2n-4} $$\displaystyle +...+ \left(\begin{array}{c}2n\\2n-2\end{array}\right)3^2+ \left(\begin{array}{c}2n\\2n-1\end{array}\right)3$

    this is the the expand of

    $\displaystyle (1+3)^{2n}$
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum